Prevalence of Concomitant Use of Angiotensin Converting Enzymes Inhibitors and Angiotensin Receptors Blockers: A Retrospective Study - Alhawiti, Alhanouf; Saleem, Mohamed TS; Abdelazeem, Ahmed Hasan; Rahbeni, Tahani Al (International Journal of Pharmaceutical Investigation, 2026)
Background A retrospective study was conducted using Electronic Health Records (EHRs) from several hospitals in Saudi Arabia. Materials and Methods All hypertensive patients who visited the hospitals between 2016 and 2022 and received at least one drug from the ACE inhibitor or angiotensin receptor blocker category were included in the study. Demographic variables and treatment regimens were collected from the real-world evidence research network available at the SFDA. Results The study found that of the total number of medical prescriptions during the study period (2016-2022), was 55.1% of ACEIs and 44.9% of ARBs. The most commonly used medications in the ACEI group were captopril, enalapril, fosinopril, perindopril, lisinopril, ramipril, and quinapril. In the ARB group, the most commonly used medications were olmesartan, candesartan, irbesartan, eprosartan, losartan, and telmisartan. The analysis of the data also revealed the frequency of prescription use for ACEIs and ARBs in each year. The most frequent use of ACEI prescriptions was in 2019, while for ARBs, it was in 2018. The study also identified 2,706 patients who concurrently used ACEIs and ARBs, with a higher percentage in females. The median age of these patients was 61 years. Regarding the number of exposure times and episodes, the year 2019 had the highest frequency, followed by 2018 and 2017. The incidence rate per 10,000 patient years was highest in 2016. Conclusion The prevalence of concomitant use is still detected but at a low rate. This reflects adherence to the implementation of risk reduction measures by the Saudi Food and Drug Authority.
Keywords: Angiotensin Converting Enzymes Inhibitors; Angiotensin Receptors Blockers; Acute Kidney Injury; Hypertension; Combination Therapy.